Population parameters and feeding biology of sergestid shrimp, Lucifer hanseni, from Tebrau Straits, Malaysia - Osman, Norhafizah (2013)
A study on Lucifer population was conducted to examine their population dynamics and feeding habit. Growth, mortality, recruitment, status of the stock and feeding habits of Lucifer hanseni were examined from five stations along the Tebrau Straits, Johor, Malaysia during November 2009 to October 2010. Two stations were located in Pendas River and its estuary, while three others were established Tebrau Straits with different habitat characteristics viz. fringing mangroves, sea grass bed and open water. Sampling station was approximately 1 km apart from each other. The specimens were collected during high tide by subsurface towing of a bongo net (mesh size of 500 μm) for 20 minutes. The samples were then preserved in 5% formalin and brought back to the laboratory for analysis. The growth, mortality and recruitment of L. hanseni were investigated based on monthly length-frequency data, using FiSAT software. The results showed that average natural mortality (2.84 yr-1) was higher than the average value of fishing mortality (1.20 yr-1) indicating the imbalance position in the stock. The value for exploitation level (E) was 0.30. This indicates that the fishery of L. hanseni in the Tebrau Straits is still under exploited. This is based on the assumption that a stock is optimally exploited when fishing mortality (F) equals natural mortality (M), or E = (F/Z) = 0.5. The annual recruitment of L. hanseni showed continuous recruitment with three major peaks observed in March, July and October. The peaks were possibly affected by environmental factors and the availability of food source. Feeding habits and diet composition of L. hanseni were also investigated. A total of 600 guts were examined using standard method of gut content studies. Diet composition was categorized into five main groups which were phytoplankton, zooplankton, macroalgae, debris, and unidentified materials. According to simple resultant index (%SRI), the highest percentage of food components was debris (42.76%) followed by phytoplankton (34.96%), zooplankton (12.56%), unidentified materials (5.80%) and macroalgae (3.93%). Phytoplankton was mainly made up of Nitzschia sp., Dactylococcopsis sp., Synedra sp., Gonylaux sp., Peridinium sp., Coscinodiscus sp., Navicula sp. and Rhizosolenia sp. while the zooplankton was comprised of appendages of crustacean, appendages of copepod, nauplii and cladocerans. The various composition of food items proved that L. hanseni is an opportunistic omnivorous. Lucifer hanseni can possibly switch their food preference depends on the abundant types of food available at that particular time.